Introspection of agroecology for food systems from agroforestry perspective - Ramanan S., Suresh; Arunachalam, A. (Indian Journal of Agroforestry, 2021)
Food is a vital need for all humans and efforts to meet out our food demand through an industrialized agricultural approach has damaged our land and environment. Globally, sustainability is gaining momentum in all sectors of life with many countries committed to achieve the UN Sustainable Development Goals (SDG) by 2030. Sustainability in the agriculture sector is also gaining prominence which is reflected in the popularity of terms like organic agriculture, conservation agriculture smart-farming, zero-budget natural farming etc. Ultimately, all these are means to develop holistic food systems that follow 13 principles of agroecology. Agroecology as a science focusses on the ecology of the food system. Given that, United Nations is convening a Global Food Submit in 2021 and researchers are emphasizing that our present food system should adhere to the principles of agroecology. The present introspection study revealed that agroforestry has more relevance to the scientific domain of Agroforestry and was observed to adheres to 9 of 13 agroecological principles.